ANALISIS PENGELOLAAN PIUTANG DAN POTENSI PIUTANG YANG TIDAK TERTAGIH SEBAGAI TINDAK LANJUT KEBIJAKAN PEMBAYARAN KREDIT PADA BIMBINGAN BELAJAR X DI MADIUN - Rizka Hardiyanti (INVENTORY: JURNAL AKUNTANSI, 2017)
This study aims to analyze the management accounts and the potential doubtful as a follow-up loan payments policy on tutoring X in Madiun. Accounts receivable is one type of accounting transactions dealing with the billing of consumers is owed on a person, a company, or an organization for goods and services that has been given to the consumer. Results of research conducted at the Institute of tutoring X in Madiun, the researchers conclude that the management of receivables and the potential doubtful at a tutoring agency X in Madiun there have been improvements in the new school year 2016-2017. So in the new academic year 2015-2016 is no longer doubtful,    but still no payment policy on credit to be paid each maturity. Keywords: Receivables Management, Potential Accounts Receivables photo and Follow-Up Credit Policy